HIV Treatment as Prevention: Implications for Health Promotion. (8th October 2016) - Slavin, Sean
Abstract: Evidence has been accumulating in recent years that individuals with HIV who are effectively treated with antiretroviral drugs are highly unlikely to transmit the virus to their sexual partners. This approach has great potential to contribute to ongoing prevention efforts and has been termed 'treatment as prevention'. International political momentum has been building in recent years to attempt to significantly reduce new HIV infections globally and end the epidemic by 2030. In pursuit of such aims a number of local health authorities and communities have adopted intensified 'test and treat' strategies to quickly diagnose infections and reduce the risk of onward transmission through an immediate offer of treatment. These have most commonly been driven through enhancements to clinical services and health promoters have been engaged in limited ways. People with HIV often have high rates of health literacy and are now expressing interest in knowing more about how treatment as prevention might work to reduce their individual risk of sexual transmission. For some this represents an added risk reduction measure and for others it may replace condoms. There is currently an opportunity for health promotors to engage with this approach both to exploit its prevention benefits and to counter the stigma that attaches to HIV infectiousness. It is hoped that any reduction in stigma and fear of transmission will help improve the quality of social and sexual relationships among affected groups.